Evaluating rutting on porous aspalt mixes-comparison between Mashall and superpave method in terms of volumetric properties [electronic resource] - 212855 Han, Teong Eng; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Jalan dan Pengangkutan)) - Universiti Teknologi Malaysia, 2007